2008
DOI: 10.1080/14786410701848154
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition ofSchinus molleessential oil and its cytotoxic activity on tumour cell lines

Abstract: The leaf essential oil hydrodistilled from Schinus molle grown in Costa Rica was characterised in terms of its chemical composition, antioxidant activity, ability to induce cytotoxicity and the mechanism of cell death involved in the process. As a result, 42 constituents, accounting for 97.2% of the total oil, were identified. The major constituents of the oil were beta-pinene and alpha-pinene. The antioxidant activity showed an IC(50) of 36.3 microg mL(-1). The essential oil was cytotoxic in several cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 21 publications
3
42
0
4
Order By: Relevance
“…Based on some evidence that extracts (Ruffa et al, 2002) and essential oils (Díaz et al, 2008) from Schinus species showed in vitro cytotoxicity effects, the obtained crude oil from leaves of S. terebinthifolius was thus evaluated against five different tumoral cell lineages. Dose-response curves were generated and IC 50 values were calculated for this active oil against five cell lines (B16F10-Nex2, A2058, HeLa, MCF7 and HL-60), as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Based on some evidence that extracts (Ruffa et al, 2002) and essential oils (Díaz et al, 2008) from Schinus species showed in vitro cytotoxicity effects, the obtained crude oil from leaves of S. terebinthifolius was thus evaluated against five different tumoral cell lineages. Dose-response curves were generated and IC 50 values were calculated for this active oil against five cell lines (B16F10-Nex2, A2058, HeLa, MCF7 and HL-60), as shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…[89] On the other hand, there are numerous studies showing the toxicity of essential oils and active components of essential oils, for example, origanum essential oil exhibited high levels of cytotoxicity against four permanent animal cell lines including two derived from human cancers, [90] Melissa officinalis essential oil exhibited cytotoxicity against human cancer cell lines (A549, MCF-7, Caco-2, HL-60, K562) and a mouse cell line (B16F10), [91] Schinus molle essential oil was cytotoxic on breast carcinoma and leukemic cell lines by a mechanism related to apoptosis. [92] Transdermal systemic toxicity of permeation enhancers: essential oils and their compounds Toxicity of essential oils and their active constituents to a large extent depends on their concentration and chemical structure. Therefore, fairly toxicological and applicable studies let get a clear answer about their safety and use as enhancers for drug permeation through the skin.…”
Section: Antitumor Activity Of Essential Oils and Their Compoundsmentioning
confidence: 99%
“…GOFF & KLEE (2006) have proposed that spices can be used to improve food preservation. In DIAZ et al (2008) the essential oil of the leaf of Schinus molle was constituted mainly by the monoterpenoids a-and b-pinene. The essential oil studied showed citotoxity against Breast carcinoma cell line and also against Leukemic cell line K562 (DIAZ et al, 2008).…”
Section: % --------------------------Compounds Present In the Most mentioning
confidence: 99%
“…In DIAZ et al (2008) the essential oil of the leaf of Schinus molle was constituted mainly by the monoterpenoids a-and b-pinene. The essential oil studied showed citotoxity against Breast carcinoma cell line and also against Leukemic cell line K562 (DIAZ et al, 2008). Capsaicin is the predominant compound in pungent peppers of Capsicun genera and is known to induce depletion of substance P and other neuropeptides from sensory nerve terminals (PALEVITCH & CRAKER, 1995).…”
Section: % --------------------------Compounds Present In the Most mentioning
confidence: 99%